Multibeam Compact Reflectarray Antenna With Low Scan Loss and Wide-Angle Performance Using a Multi-Feed Configuration - Andres Gomez-Alvarez; Alvaro F. Vaquero; Manuel Arrebola; Marcos Rodriguez Pino (IEEE Open Journal of Antennas and Propagation)
In this article, two multibeam reflectarray antennas are presented for Ka-band in a multi-feed configuration. Both feature a wide-angle scanning range with very low scan losses. They are designed using an iterative optimization process based on a phase-only optimization (POO) which allows fine control over the gain for each beam. The phase responses of the lattice cells are selected taking into account the illumination levels and radiation requirements of all feeds in the system. Minimization of scanning losses and overall antenna compactness are prioritized in the design. The feeding elements are placed along a tilted arc with a low F/D of 0.58. Compared to other beam scanning reflectarray designs in the literature, inter-feed blockage is avoided and thus simultaneous multibeam operation is supported. The two reflectarray designs are implemented using a unit cell with low losses and high angular stability, and they operate in different orthogonal linear polarizations. They are manufactured and measured, showing very low scan losses of 0.5 dB and 1.4 dB across a ±45-degree scanning range, while having maximum gain levels of 28.2 dBi and 29.4 dBi respectively. Moreover, they present extremely low beam squint across the evaluated 3 GHz band, and a measured 1 dB fractional bandwidth over 6.8% and 10%.